Effect of amphoteric dopant on the dielectric and structural properties of yttrium doped potassium sodium niobate thin film - Mohd Hatta, Maziati Akmal; Abd Rashid, Mohd Warikh M.; Azlan, Umar Al Amani; Azam, Mohd Asyadi; Ismail, Syahriza (Elsevier, 2016)
The amphoteric dopant effects on dielectric and structural properties of KNN were studied. The trace amounts of dopant were incorporated into the KNN lattice and formed the orthorhombic perovskite structure. The distribution of yttrium dopant on the perovskite lattice is responsible for enhancement of dielectric behaviors of KNN films. The dielectric loss is reduced from 0.18% to 0.0125%, owing to the distribution of yttrium dopant at A-site lattice. Meanwhile, the tendency of Y3þ to occupy the B-site lattice at high dopant concentration causes an increase in dielectric loss. The particles size of the KNN at 0.5 mol% yttrium was found to be uniform while porous structures were formed with increasing dopant concentration.